Physical Infrastructure and Economic Growth in Nigeria - Habeeb Olaniyi Olayiwola (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
This study investigated the nexus between physical infrastructure and economic growth in Nigeria for the period of 1986 - 2020. The data such as Gross Domestic Product (GDP) growth rate (proxy of economic growth), electricity production, road and rail lines, air transport and telecommunication infrastructure were considered for the study. The data were culled from World Development Indicator (WDI). The techniques such as descriptive statistics, correlation analysis, ADF unit root test, co-integration test, Autoregressive Distributed Lag (ARDL) and diagnostic tests were employed to analyze the data collated. The findings show the existence of short run relationship between physical infrastructure and economic growth in Nigeria. However, physical infrastructure has no relationship with economic growth in Nigeria in the long run. The study concludes that physical infrastructure is an indisputable ingredient for the growth process in the short run. In fact, it is an engine of growth and lubricant for obstacles of attracting foreign investments into Nigerian economy. It was therefore recommended among others that Nigerian government should focus on the improvement of road and electricity production if truly the country wishes to be among the top 20 economies of the world as stipulated in the failed vision 2020.